Cross-Border Tourism Development in the Thai-Lao Border Area of Tha Li - Luang Prabang - Saiyasopon, Sukhumvit; Pakittawichit, Thananchakorn; Mankan, Wipat; Meenongwah, Suchao (Interdisciplinary Academic and Research Journal, 2023)
Background and Aims: In many countries, the government places a significant emphasis on the tourism industry, as it remains one of the few industries with the potential for expansion and bringing income into the country. This research is an exploratory study with the following objectives 1) To assess the policies and development plans for cross-border tourism between Thailand and Laos in the Tha Li-Luang Prabang area. 2) To examine the context of tourism management and the current state of cross-border tourism between Thailand and Laos in the Tha Li-Luang Prabang area by surveys in the Tha Li-La District-Saiyaburi-Luang Prabang area. Methodology: The research employed for this study is characterized by a multifaceted approach. It commences with a comprehensive review of various documents, encompassing national-level strategic plans, provincial-level strategies, regional initiatives, and a detailed exploration of tourist destinations. Furthermore, a pivotal aspect of this research involves the meticulous assessment and analysis of tourism potential in both regions. Valuable perspectives and insights are actively sought from a diverse array of stakeholders, including senior executives and dedicated professionals involved in the tourism sector, hailing from both public and private sector organizations in Loei Province. These esteemed entities comprise the Loei Provincial Strategic Office, Loei Sports and Tourism Office, as well as the Special Area Office for Sustainable Tourism Development in Loei (OPD.5). Additionally, input is graciously extended to the Loei Province Tourism Business Association, the Tourism Authority of Thailand Loei Office (TAT Loei), the Loei Chamber of Commerce, and esteemed counterparts in the Lao PDR. In the neighboring Lao PDR, participation is actively welcomed from the Ministry of Tourism and Culture, Lao PDR Tourism Business Association, and tourism departments at the provincial and municipal levels using the standard survey methodology for Thai tourism destinations. Result: Regarding policies and development plans for cross-border tourism between Thailand and Laos in the Tha Li-Luang Prabang area, Loei Province has established a strategic initiative called the "Special Area Tourism Development Project - Loei Linkage with Neighboring Countries." The Loei Provincial Administrative Organization (Loei PAO) has been assigned to collaborate and plan the connecting tourism routes along the Mekong River between Loei Province and the Lao People’s Democratic Republic (LPDR), including joint tourism activities each year. The tourism situation in Loei Province, within the Tha Li District area, lacks a systematic approach. The primary cross-border activities occur at the Nakhagaseg checkpoint, mainly for trade, medical visits, and a small fraction (only 0.5% of the total) for tourism purposes. The Luang Prabang District, a World Heritage Site and a tourist destination is the main attraction for tourists. Other tourism destinations in the area lack sufficient appeal to attract tourists effectively. Overall, the research highlights the need for more comprehensive and organized efforts to promote cross-border tourism in the Tha Li-Luang Prabang area, including the development of tourism attractions and facilities to draw tourists beyond the Luang Prabang District. Conclusion: The results of the research found that in the Tholi-Luang Prabang area of Loei Province, there is a tourism strategy that links with neighboring countries and in coordination with the Lao PDR, emphasizing connections in the Mekong River. But the tourism situation in Tha Li District is not yet systematic and border crossings at the Nakaseng checkpoint account for only 0.5 percent of travelers entering and leaving the country. Thus, with an emphasis on trade and hospital treatment, only Luang Prabang has the potential to attract tourists as a world heritage city and tourist destination.